Multiple roles for laccase2 in butterfly wing pigmentation, scale development, and cuticle tanning. Issue 4 (27th July 2020) - Peng, Ceili L.; Mazo‐Vargas, Anyi; Brack, Benjamin J.; Reed, Robert D.
Abstract: Lepidopteran wing scales play important roles in a number of functions including color patterning and thermoregulation. Despite the importance of wing scales, however, we still have a limited understanding of the genetic mechanisms that underlie scale patterning, development, and coloration. Here, we explore the function of the phenoloxidase‐encoding gene laccase2 in wing and scale development in the nymphalid butterfly Vanessa cardui . Somatic deletion mosaics of laccase2 generated by CRISPR/Cas9 genome editing presented several distinct mutant phenotypes. Consistent with the work in other nonlepidopteran insect groups, we observed reductions in melanin pigmentation and defects in cuticle formation. We were also surprised, however, to see distinct effects on scale development including complete loss of wing scales. This study highlights laccase2 as a gene that plays multiple roles in wing and scale development and provides new insight into the evolution of lepidopteran wing coloration. Abstract :